SISTEM INFORMASI GEOGRAFIS PEMETAAN LAHAN PERTANIAN BAWANG MERAH DENGAN METODE K-MEANS CLUSTERING BERBASIS WEBSITE (Studi Kasus di Kabupaten Nganjuk) - Zuyyinal Haqqul Barir , Much; Imam Agung, Achmad; Mashuri, Chamdan (Inovate, 2019)
Geographic Information system (GIS) is a type of system that can be used for mapping the garlic farm land.The system consists of hardware, software, geographic location and human resources that can effectivelyprocess and display geographic information data. Agricultural land is an economic resource that isrelatively permanent availability, but its needs continue to increase due to development needs. The purposeof this research is tobuild SIG -based GIS Website and M-energy method of K-means Clustering for themapping of garlic farmland . The method used In this research is qualitative and uses K-means Clusteringfor GIS. This method is used for grouping data that has similarity variables. This method generates severaliterations that have clustervalues. Of These iterations used the least cluster value to determine theagricultural Land Mapping group. The result of this research is a geographic information system that canmap the garlic farm land. GIS testing was conducted on land in 20 sub-districts in Nganjuk district withconsideration of 3 variables and the test count 4 times. From The test results, the average number ofconformity calculation is obtained by 93,51% between manual counting result and counting result usingSIG.Keywords: K-means, Clustering, shallots, land mapping.